From professional bureaucracy to competitive bureaucracy – redefining universities’ organization principles, performance measurement criteria, and reason for being - Kallio Tomi J.; Kallio Kirsi-Mari; Blomberg Annika (Emerald, 2022)
Purpose
This purpose of this study is to understand how the spread of audit culture and the related public sector reforms have affected Finnish universities’ organization principles, performance measurement (PM) criteria and ultimately their reason for being.
Design/methodology/approach
Applying extensive qualitative data by combining interview data with document materials, this study takes a longitudinal perspective toward the changing Finnish higher education field.
Findings
The analysis suggests the reforms have altered universities’ administrative structures, planning and control systems, coordination mechanisms and the role of staff units, as well as the allocation of power and thus challenged their reason for being. Power has become concentrated into the hands of formal managers, while operational core professionals have been distanced from decision making. Efficiency in terms of financial and performance indicators has become a coordinating principle of university organizations, and PM practices are used to steer the work of professionals. Because of the reforms, universities have moved away from the ideal type of professional bureaucracy and begun resembling the new, emerging ideal type of competitive bureaucracy.
Originality/value
This study builds on rich, real-life, longitudinal empirical material and details a chronological description of the changes in Finland’s university sector. Moreover, it illustrates how the spread of audit culture and the related legislative changes have transformed the ideal type of university organization and challenged universities’ reason for being. These changes entail significant consequences regarding universities as organizations and their role in society.